Life-cycle greenhouse gas emissions and net energy assessment of large-scale hydrogen production via electrolysis and solar PV. Issue 10 (24th August 2021) - Palmer, Graham; Roberts, Ashley; Hoadley, Andrew; Dargaville, Roger; Honnery, Damon
Abstract : Environmental impacts and net-energy of hydrogen production via solar-electrolysis are highly sensitive to operating constraints and context specific variances. Abstract : Water electrolysis powered by solar photovoltaics (PV) is one of several promising green hydrogen production technologies. It is critical that the life cycle environmental impacts and net energy balance are assessed to ensure that solar-electrolysis can contribute to the deep decarbonisation of global energy. Life cycle assessment (LCA) and net energy analysis (NEA) are tools for environmental and net energy assessment of such technologies. LCA/NEA studies of renewable hydrogen typically include simplifying assumptions, such as steady state operation under average conditions. Whilst simplifications may be necessary for preliminary analysis, marked differences arising from context specific variances and operating constraints may be overlooked. To address this gap, we conduct an LCA/NEA of a hypothetical large-scale solar-electrolysis plant, with a focus on operational sensitivities. We find the most significant component is the solar modules due to the materials and processes used in their manufacture. We find the most significant sensitivity stems from the electrolyser turndown and the commensurate need to buffer solar electricity with storage or grid electricity. Under baseline conditions, the greenhouse gas (GHG) emissions are around one-quarter that of the currently dominant process for hydrogen production, steam methane reforming (SMR). However, sensitivity analysis shows that GHG emissions may be comparable to SMR under reasonably anticipated conditions. Net energy results are less than for fossil fuels and sufficiently uncertain to warrant further attention. We recommend that LCA and NEA are integrated with project planning to ensure that hydrogen meets the goals of green production.